Peran Pendidikan Agama Islam dalam Pembentukan Karakter dan Etika Siswa - Nabila, Salma; Bariah, Oyoh; Makbul, M (Peneliti.net, 2023)
This study aims to investigate the important role of Islamic Religious Education in the process of shaping students' character and ethics. In the current era of globalization and modernization, Islamic religious education plays a significant role in shaping students' character and ethics. The literature review method was used in this study to analyze relevant literature on the role of Islamic religious education in shaping students' character and ethics. The findings show that Islamic religious education plays a role in instilling ethical values, developing positive attitudes and behaviors, strengthening religious identity, and integrating with other curricula. The implication of this research is the importance of developing effective programs and policies to improve the quality of Islamic religious education in Indonesia. This research provides an in-depth understanding of the important role of Islamic religious education in the formation of student character and ethics. Keywords: Character Building, Islamic Religious Education, Student Ethics